Los parabenos y sus efectos en la reproducción femenina - Quezadas Fuentes, Juan Manuel (Universidad Autónoma Metropolitana, 2021)
Anthropogenic (Human Activities) have generally been reported to have a negative impact in the environment, these human activities can damage the correct balance at different levels in the ecosystems, affecting the diversity of life on the planet, compromising the survival of the human species. For the last 150 years, with the beginning of the industrial revolution and its exponential growth around of the world, companies such as pharmaceuticals, agri-food, construction or manufacturing release into the environment, among other things, greenhouse gas emissions such as carbon dioxide (CO2), methane and another’s by-products potentially toxic, which when in contact with humans can generate changes in our health, promoting the development of chronic degenerative diseases. In addition, it become normal in our life the use of substances in processed products such as food, medicine or articles of personal hygiene with the intention of extending their useful life and maintaining their functional characteristics for longer. Such is the case of parabens (PBs), Parabens are homologous esters of para-hydroxybenzoic acid. The various representatives of this substance class differ only in the structure of their alkyl radicals, they are used in a wide variety of products including shampoos, lotions, deodorants, fungicidal and as antibacterial, therefore its addition to various products has increased in the recent last 50 years. Despite they have been considered safe and of low toxicity, recent studies have shown that their presence in the body may be related with the increase of some types of cancer and the deterioration of health reproductive.; Se ha descrito que las actividades antropogénicas generalmente tienen un impacto negativo en el ambiente, que pueden dañar a diferentes niveles el correcto balance de los ecosistemas afectando la diversidad de la vida en el planeta, comprometiendo la supervivencia de la especie humana. Durante los últimos 150 años con el inicio de la revolución industrial y su exponencial crecimiento alrededor del mundo, empresas como el farmacéutico, el agroalimentario, de construcción o de manufactura liberan al medio, entre otras cosas, gases de efecto invernadero como el dióxido de carbono (CO2), metano y subproductos potencialmente tóxicos, que al estar en contacto con los seres humanos pueden generar cambios a la salud del organismo promoviendo el desarrollo de enfermedades crónico-degenerativas. Además, se ha normalizado el uso de aditivos en productos procesados como alimentos, medicamentos o artículos de higiene personal con la intención de alargar su vida de útil y que estos mantengan sus características funcionales durante más tiempo. Tal es el caso de los parabenos (PBs), estas son moléculas derivadas del ácido para-hidroxibenzoico constituidas por un anillo fenólico y una cadena de alquilo, con capacidad fungicida y antibacterial, por lo que su adición a diversos productos se incrementó en los últimos 50 años. Aunque se han considerado seguros y de baja toxicidad, estudios recientes han puesto en evidencia que pueden estar relacionados con el incremento de algunos tipos de cáncer y en el deterioro de la salud reproductiva.